Multi-frequency VEMPs improve detection of present otolith responses in bilateral vestibulopathy - Lucieer, F.; van der Lubbe, M.; van Stiphout, L.; Janssen, M.; Van Rompaey, V.; Devocht, E.; Perez-Fornos, A.; Guinand, N.; van de Berg, R. (Frontiers in Neurology, 2024)
Objective To investigate whether multi-frequency Vestibular Evoked Myogenic Potential (VEMP) testing at 500, 750, 1,000, and 2,000 Hz, would improve the detection of present dynamic otolith responses in patients with bilateral vestibulopathy (BV). Methods Prospective study in a tertiary referral center. BV patients underwent multi-frequency VEMP testing. Cervical VEMPs and ocular VEMPs were recorded with the Neuro-Audio system (v2010, Neurosoft, Ivanovo, Russia). The stimuli included air-conducted tone bursts of 500, 750, 1,000, and 2,000 Hz, at a stimulation rate of 13 Hz. Outcome measures included the percentage of present and absent VEMP responses, and VEMP thresholds. Outcomes were compared between frequencies and type of VEMPs (cVEMPs, oVEMPs). VEMP outcomes obtained with the 500 Hz stimulus, were also compared to normative values obtained in healthy subjects. Results Forty-nine BV patients completed VEMP testing: 47 patients completed cVEMP testing and 48 patients completed oVEMP testing. Six to 15 % more present VEMP responses were obtained with multifrequency testing, compared to only testing at 500 Hz. The 2,000 Hz stimulus elicited significantly fewer present cVEMP responses (right and left ears) and oVEMP responses (right ears) compared to the other frequencies (p ≤ 0.044). Using multi-frequency testing, 78% of BV patients demonstrated at least one present VEMP response in at least one ear. In 46% a present VEMP response was found bilaterally. BV patients demonstrated a significantly higher percentage of absent VEMP responses and significantly higher VEMP thresholds than healthy subjects, when corrected for age (p ≤ 0.002). Based on these results, a pragmatic VEMP testing paradigm is proposed, taking into account multi-frequency VEMP testing. Conclusion Multi-frequency VEMP testing improves the detection rate of present otolith responses in BV patients. Therefore, multi-frequency VEMPs should be considered when evaluation of (residual) otolith function is indicated.